THE YOUNGER GENERATION IS A SOURCE OF INSPIRATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article is devoted to the assessment of modern youth of their social qualities. Based on the analysis of empirical data, the authors conclude that the social portrait of today's youth has distinctly contradictory features. Representatives of the younger generation adequately and objectively assess their positive and negative qualities.